Magnetoresistive Single-Molecule Junctions: The Role of the Spinterface and the Ciss Effect - Aravena-Ponce, D; Aravena-Ponce, D (John Wiley and Sons Inc, 2022)
This review is an effort in putting together the latest results about room-temperature magnetoresistive (MR) effects in nanoscale/single-molecule electronic devices consisting of one (few) molecule(s) placed in electrical contact between two nanoscale electrodes. Molecules represent powerful building blocks for developing state-of-the-art MR devices, as they bring long spin relaxation timescales, low cost and high tunability of their electrical and magnetic properties via chemical modifications. The capability to control at room temperature and under bespoke electrodes’ magnetization the MR response of a single-molecule (SM) device has been a longstanding quest. Such SM platforms could serve as fundamental tools to understand what the main mechanistic ingredients of MR effects in a molecular device are, leading to their use as building-blocks for miniaturization in spintronic applications. The work carried out so far in this field has identified two key components directly involved in the MR response of a single(few)-molecule(s) device: (i) The molecule|electrode spinterface, defining the interplay between interfacial electrostatics and spin density, has been proven to play a fundamental role in the interpretation of the observed single-molecule junction s MR effects, which is governed by the electrode material and the electrode-molecule chemistry. (ii) Two aspects of the molecular structure have been demonstrated to be involved in the spin-dependent conduction mechanism: (1) the presence of paramagnetic metal centres in the molecular structure and how their orbitals bearing the unpaired electrons couple with the device electrodes, and (2), the degree of chirality within the molecular wire. This contribution will focus on the above points (i-ii) by making use of specific examples in the literature. © 2022 The Authors. Israel Journal of Chemistry published by Wiley-VCH GmbH.